Comparison between pea and soy protein‐based bioplastics obtained by injection molding. Issue 20 (23rd December 2020) - Jiménez‐Rosado, Mercedes; Rubio‐Valle, Jose Fernando; Perez‐Puyana, Víctor; Guerrero, Antonio; Romero, Alberto
Abstract: The elaboration of bioplastics from renewable polymers (e.g., proteins) is a field with great potential for industrial applications such as food packaging and agriculture. This study evaluates the development of bioplastic systems by injection molding using two different raw materials: soy protein isolate (SPI) and pea protein isolate (PPI). Both proteins are by‐products, which lowers the price of processed bioplastics. However, it is necessary to control their properties during the manufacture processing, in order to ensure that they can replace conventional plastics. Therefore, the main objective of this work was to compare the properties of SPI and PPI bioplastics processed at different injection times (150, 300, and 450 s) and different mold temperatures (70 and 130°C). Thus, mechanical properties, water uptake capacity, and transparency were evaluated. The results show the potential of these raw materials to produce bioplastics that can replace conventional plastics, and that the processing conditions can be modified to obtain the desired final properties. Abstract : This work is focus on the development of soy and pea protein‐based bioplastics using different parameters (injection time and mold temperature) in their processing by injection molding.